Good governance, political experiences, and public support for mandatory sentencing: Evidence from a progressive US state - Sundt, Jody L. (Punishment & society, 2019)
A shift in public mood and declining incarceration rates in the United States signal a potential change in the politics of punishment. This research considers whether the public continues to support mandatory sentencing. The study expands upon existing knowledge by testing theoretical predictions about how instrumentalism, political beliefs, and political participation affect public support for mandatory sentences. Drawing on a state-wide survey of 1569 adults from Oregon, the study found that belief in the effectiveness of prosecutors, judges, and prisons significantly influenced support for mandatory sentencing. Although 67% of those surveyed favored judicial discretion, a firm belief that “prisons work” may limit efforts to reduce incarceration and roll back mandatory sentences.